Health disparities in one of the world's most progressive countries: a scoping review of mental health and substance use among sexual and gender minority people in the Netherlands - Tonda L. Hughes; Lauren Bochicchio; Laurie Drabble; Maaike Muntinga; Jan S. Jukema; Cindy B. Veldhuis; Sunčica Bruck; Henny Bos (BMC, 2023)
Abstract Background Evidence from many parts of the world shows that sexual and gender minority (SGM) people have poorer health than their cisgender heterosexual counterparts. Minority stressors, particularly stigma and discrimination, have been identified as major contributors to sexual orientation- and gender identity-related health disparities, particularly negative mental health and behavioral health outcomes. To better understand factors that contribute to these disparities, we conducted a scoping review of SGM mental health and substance use research in the Netherlands-a country with a long-standing reputation as a pioneer in SGM equality. Methods Using Joanna Briggs Institute guidelines and the PRISMA-ScR protocol, we searched seven databases to identify studies published between 2010 and 2022 that focused on substance use and/or mental health of SGM youth and adults in the Netherlands. Results Although there was some evidence that SGM people in the Netherlands report fewer substance use and mental health concerns than those in less progressive countries, with very few exceptions studies found poorer outcomes among SGM participants than cisgender, heterosexual participants. However, this observation must be considered cautiously given major gaps in the literature. For example, only one study focused exclusively on adult sexual minority women, two focused on older SGM adults, and very little attention was given to nonbinary individuals. Most studies used non-probability samples that were quite homogenous. Many studies, especially those with youth, assessed sexual orientation based on sexual attraction; some studies of adults operationalized SGM status as having a same-sex partner. Importantly, we found no studies that directly assessed associations between structural-level stigma and health outcomes. Studies were mostly focused at the individual level and on health problems; very little attention was given to strengths or resilience. Conclusions Findings of persistent health disparities-despite the relatively long history of SGM supportive policies in the Netherlands-highlight the need for more research and greater attention to population groups that have been underrepresented. Such research would not only provide guidance on strategies to improve the health of SGM people in the Netherlands, but also in other countries that are seeking to reduce health inequities. Addressing SGM health disparities in the Netherlands and elsewhere is complex and requires a multifaceted approach that addresses individual, interpersonal and structural factors.